A SLUGGS and Gemini/GMOS combined study of the elliptical galaxy M60: wide-field photometry and kinematics of the globular cluster system - Faifer, Favio Raúl (2015)
We present new wide-field photometry and spectroscopy of the globular clusters (GCs) around NGC 4649 (M60), the third brightest galaxy in the Virgo cluster. Imaging of NGC 4649 was assembled from a recently obtained Hubble Space Telescope/Advanced Camera for Surveys mosaic, and new Subaru/Suprime-Cam and archival Canada-France- Hawaii Telescope/MegaCam data. About 1200 sources were followed up spectroscopically using combined observations from three multi-object spectrographs: Keck/Deep Imaging Multi-Object Spectrograph, Gemini/Gemini Multi-Object Spectrograph and Multiple Mirror Telescope/Hectospec. We confirm 431 unique GCs belonging to NGC 4649, a factor of 3.5 larger than previous data sets and with a factor of 3 improvement in velocity precision. We confirm significant GC colour bimodality and find that the red GCs are more centrally concentrated, while the blue GCs are more spatially extended. We infer negative GC colour gradients in the innermost 20 kpc and flat gradients out to large radii. Rotation is detected along the galaxy major axis for all tracers: blue GCs, red GCs, galaxy stars and planetary nebulae. We compare the observed properties of NGC 4649 with galaxy formation models. We find that formation via amajor merger between two gas-poor galaxies, followed by satellite accretion, can consistently reproduce the observations of NGC 4649 at different radii. We find no strong evidence to support an interaction between NGC 4649 and the neighbouring spiral galaxy NGC 4647. We identify interesting GC kinematic features in our data, such as counter-rotating subgroups and bumpy kinematic profiles, which encode more clues about the formation history of NGC 4649.